1995
DOI: 10.1002/bdd.2510160904
|View full text |Cite
|
Sign up to set email alerts
|

Interspecies pharmacokinetic scaling of BSH in mice, rats, rabbits, and humans

Abstract: Sodium mercaptoundecahydrododecaborate or BSH is an important compound for boron neutron capture therapy (BNCT). The total clearance and steady state volume of distribution of BSH in humans and in laboratory animals were analyzed as a function of species body weight using the allometric equation for interspecies scaling. Significant linear relationships were obtained between log CLt (Lh-1) and log W (kg) (r = 0.972; p = 0.028) as well as log VSS (L) and log W (kg) (r = 0.999; p = 0.0005). The corresponding all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 20 publications
1
11
0
4
Order By: Relevance
“…Furthermore, it is known that some BCCs tend to accumulate in the myocardium, bones, nails and hair (Mehta, 1995;Murray, 1998). Some studies suggest that kinetics is similar among mammals, but some researchers have found slight differences between rodents, particularly in renal depuration, and they suggest the importance of paying attention to these differences and therefore of being very careful in applying the conclusions from these studies to humans (Dourson, 1998;Pahl, 2005).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, it is known that some BCCs tend to accumulate in the myocardium, bones, nails and hair (Mehta, 1995;Murray, 1998). Some studies suggest that kinetics is similar among mammals, but some researchers have found slight differences between rodents, particularly in renal depuration, and they suggest the importance of paying attention to these differences and therefore of being very careful in applying the conclusions from these studies to humans (Dourson, 1998;Pahl, 2005).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 95%
“…BCCs have also shown several advantages in regard to pharmacokinetics, including a high absorption rate, notable changes in the partition coefficient (compared to boron-free compounds with a similar structure, with the resulting effects on distribution), and the reduced feasibility of in vivo degradation (leading to the possible accumulation in specific tissues or organs) (Teshima, 1992;Mehta, 1995;Dourson, 1998;Murray, 1998;Koo, 2007;González, 2011;Tarres, 2014). Furthermore, it is known that some BCCs tend to accumulate in the myocardium, bones, nails and hair (Mehta, 1995;Murray, 1998).…”
Section: The Origins Of Avoidance Of Bccs In Medicinementioning
confidence: 97%
“…Laznicek et al (1990) 2-Iodohippurate Intravenous CL tot Laznicek et al (1990) 3-Iodohippurate Intravenous CL tot Laznicek et al (1990) 4-Iodohippurate Intravenous CL tot Laznicek et al (1998) Lidocaine Intravenous V d , CL tot , t 1=2 Lin et al (1999) Monoclonal antibody against VEGF Intravenous V d , CL tot , C max , t 1=2 Lin et al (1999) Monoclonal antobody against VEGF Subcutaneous CL tot , C max , t 1=2 Mehta and Lu (1995) BSH Intravenous V d , CL tot Mitsuhashi et al (1990) ACNU Intravenous V d , CL tot Mordenti et al (1991) rCD4 Not stated V d , CL tot Mordenti et al (1991) CD4-IgG Not stated V d , CL tot Mordenti et al (1991) rhGH Not stated V d , CL tot Mordenti et al (1991) rt-PA Not stated V d , CL tot Mordenti et al (1991) Relaxin …”
Section: Authors Substance Route Parametersmentioning
confidence: 98%
“…Kallynochrons and apolysichrons are transformed time units in elementary Dedrick plot and complex Dedrick plot, respectively. Though many investigators [12][13][14] have used the concept of species invariant time in their allometric analysis, a direct comparison of allometric approaches with species invariant time has not been systematically evaluated. Therefore, the objective of this study is to compare the predictability of allometric equations with that of species invariant time methods.…”
Section: Introductionmentioning
confidence: 99%